We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
502
2
avatar
log5(7x - 4) = log5(5x - 3) how do I solve this?
 Mar 4, 2014

Best Answer 

 #1
avatar+259 
+3
The domain of definition: 5x - 3 > 0 => x > 5/3. log5(7x - 4) = log5(5x - 3) <=> 7x - 4 = 5x - 3. The further steps are traditional.
 Mar 4, 2014
 #1
avatar+259 
+3
Best AnswerThe domain of definition: 5x - 3 > 0 => x > 5/3. log5(7x - 4) = log5(5x - 3) <=> 7x - 4 = 5x - 3. The further steps are traditional.
scrutinizer Mar 4, 2014
 #2
avatar+2353 
0
scrutinizer:

The domain of definition: 5x - 3 > 0 => x > 5/3. log5(7x - 4) = log5(5x - 3) <=> 7x - 4 = 5x - 3. The further steps are traditional.



I think you might haver made a small typo scruntinizer because 5x-3 > 0 => x > 3/5
 Mar 4, 2014

11 Online Users

avatar
avatar